Synthetic and Biosynthetic Approaches to Marine Natural Products - Barbero, Asunción (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Marine natural products containing a heterocyclic moiety in their structure are present in a wide variety of sponges, corals, algae, and fungi. Many of them show important biological activities such as cytotoxic properties against several cancer cell lines. Their challenging chemical structures have attracted the attention of many researchers who have developed various synthetic approaches. This Special Issue presents some examples of new synthetic or biosynthetic methodologies to access this type of marine natural drug.